Fiesers' reagents for organic synthesis - Ho, Tse-Lok (Wiley, 2007)
This highly successful series has provided generations of professional chemists with a comprehensive, up-to-date look at the reagent literature. The format of the series continues with its concise descriptions, good structural formulas, and selected examples of application, providing references to new reagents as well as to reagents included in previous volumes.